Human resource management - Noe, Raymond A.; Hollenbeck, John R.; Gerhart, Barry A.; Wright, Patrick M. (India : McGraw Hill, 2024)
"Our intent is to provide students with the background to be successful HRM professionals, to manage human resources effectively, and to be knowledgeable consumers of HRM products. Managers must be able to identify effective HRM practices to purchase these services from a consultant, to work with the HRM department, or to design and implement them personally"--
Includes bibliographical references and index.
Keywords: Personnel management -- United States